Electrochemical removal of phosphate in the presence of calcium at low current density: Precipitation or adsorption？. (1st February 2020) - Lei, Yang; Geraets, Emilio; Saakes, Michel; van der Weijden, Renata D.; Buisman, Cees J.N.
Abstract: Phosphorus removal and recovery from waste streams are crucial to prevent eutrophication and sustain fertilizer production. As has been shown in our previous papers, electrochemical treatment has the potential to achieve this goal. However, the adoption of electrochemical approach is limited by its high energy consumption. Here, we investigate the possibility of electrochemical phosphorus removal at extremely low current density using graphite felt as the cathode. We found a current density as low as 0.04 A/m 2 can enhance the removal of phosphate in our electrochemical system. The removal of phosphate at extremely low current density resulted from electrochemical induced calcium phosphate precipitation and not by electrochemical adsorption. Electrochemical treatment of real domestic wastewater at 0.2 A/m 2 almost eliminates the precipitation of Mg(OH)2 and limits the formation of CaCO3 . The recovered precipitates are dominated by calcium phosphate (59%), followed by 35% CaCO3 and 6% Mg(OH)2 . The specific energy consumption of this newly electrochemical system is between 4.4 and 26.4 kW h/kg P, which is 2 orders of magnitude lower than our previous system (110–2238 kW h/kg P). Key factors for this improvement prove to be enlarged precipitation area and hydroxide flux retardation by graphite felt. Practically, our study offers a potential way to reduce the energy consumption in electrochemical removal of phosphate by using a graphite felt cathode and at a current density below 0.2 A/m 2 . Fundamentally, our study contributes to the understanding of adsorption and precipitation in electrochemical removal of phosphate at an extremely low current density and with carbon-based electrodes. Graphical abstract: Image 1 Highlights: Electrochemical removal of PO4 –P at current density ≤0.2 A/m 2 is achieved. The combination of graphite felt with Pt–Ti cathode enhanced PO4 –P removal. The enhancement is built on enlarged precipitation area and lowered flux of OH − . 85% of removed calcium phosphate precipitates on graphite felt. Low current allows selectively precipitation of calcium phosphate in wastewater.